2015
DOI: 10.1111/cei.12454
|View full text |Cite
|
Sign up to set email alerts
|

Serum cytokine pattern in young children with screening detected coeliac disease

Abstract: Coeliac disease is an autoimmune disease characterized by inflammation localized to the small bowel, but less is known about systemic signs of inflammation. The aim was to measure cytokines of the T helper 1 (Th1) and T helper 2 (Th2) cell patterns in children with screening-detected coeliac disease before and after treatment with a gluten-free diet. Serum samples selected before and after the start of a gluten-free diet from 26 3-year-old children diagnosed with biopsy-proven coeliac disease and from 52 match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
31
0
5

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 37 publications
6
31
0
5
Order By: Relevance
“…Further analysis with a larger number of patients, grouped according to their disease status (active/remission after >2 years on GFD), or non-coeliac children with oral disorders should be performed to confirm and extend these preliminary results. Moreover, our findings are in agreement with the previous data describing that CD in children induced increased systemic expression of IFNc 35 . Considering that CD-induced increase of IFN-c in adults correlates with tissue damage 36 , it is worthy to speculate that the observed increase in IFN-c expression in dental pulp of CD children may also play a role in Altered trascription in dental pulp of coeliac children 353 disturbances of the dentition processes.…”
Section: Resultssupporting
confidence: 93%
“…Further analysis with a larger number of patients, grouped according to their disease status (active/remission after >2 years on GFD), or non-coeliac children with oral disorders should be performed to confirm and extend these preliminary results. Moreover, our findings are in agreement with the previous data describing that CD in children induced increased systemic expression of IFNc 35 . Considering that CD-induced increase of IFN-c in adults correlates with tissue damage 36 , it is worthy to speculate that the observed increase in IFN-c expression in dental pulp of CD children may also play a role in Altered trascription in dental pulp of coeliac children 353 disturbances of the dentition processes.…”
Section: Resultssupporting
confidence: 93%
“…Supporting this argumentation, a recent study on quality of life and compliance with GFD found that adolescents with T1D and CD, who were non‐adherent to diet had lower well‐being scores and worse glycemic control . Additionally, worse metabolic control in Ab‐pos patients might also be caused by active celiac disease with chronic inflammation . This might also be supported by the observation, that at the time of CD diagnosis and before the initiation of GFD, both groups, patients with later persistence of Ab‐positivity and patients, who later showed continuous Ab‐negativity, had higher Hba1c values than T1D‐only patients, even after adjustment for age, gender, diabetes duration and migration background.…”
Section: Discussionmentioning
confidence: 83%
“…Lately, CD in T1D is also being related to the pathogenesis of cardiovascular diseases (CVD) . Possible explanations for this might be systemic inflammation and low HDL‐cholesterol levels in T1D patients with CD . It has been reported that after initiation of a gluten‐free‐diet (GFD) HDL‐cholesterol levels increased in patients with CD .…”
Section: Introductionmentioning
confidence: 99%
“…1, 2 Pre-treatment serum vitamin D and other nutrient markers such as iron, prealbumin, and folate are significantly lower in CD individuals with villous atrophy (versus Marsh I–II histology) 3 and similarly osteopenia in CD appears to correlate with the degree of histologic severity 4 , evidenced by a greater frequency of osteopenia seen in the setting of villous atrophy rather than in potential CD where small bowel inflammation is absent. 5, 6 Although malabsorption, disturbances in parathyroid hormone secretion 79 and a chronic inflammatory state 10, 11 may be responsible for risks of bone fragility in untreated patients, bone mineral density (BMD) generally improves upon treatment of CD with a gluten-free diet (GFD) 12, 13 , particularly in children diagnosed with CD at a young age 7 , suggesting that underlying disturbances in bone mineralization may be corrected through reversal of malabsorption with treatment.…”
mentioning
confidence: 99%